WISATA BUDAYA SEBAGAI ALAT PENGUAT EKONOMI NEGARA DI JEPANG - Lina Rosliana (Diponegoro University, 2017)
Japan is known as a modern state with high technology, but still maintains its culture and traditions. This is what Japan is an interesting country to visit. The Japanese government sees the form of foreign tourists' interest to continue developing its tourism sector. Some of the policies and strategies that have been drafted by the Japanese government have yielded sweet results. Japan is the most visited country in Asia by foreign tourists, alongside Thailand and Singapore.